The pathophysiology of autoimmune blistering diseases - Yancey, Kim B. (American Society for Clinical Investigation, 2005)
Knowledge of the pathophysiology of immunobullous diseases has been advanced by the demonstration that passive transfer of antibodies against skin autoantigens can induce blisters in experimental animals with clinical, histologic, and immunopathologic features similar to those seen in human patients. In this issue of the JCI, Liu et al. extend their earlier observations regarding an experimental murine model of bullous pemphigoid by showing that the plasminogen/plasmin signaling cascade synergizes with MMP-9 during the early phase of antibody-induced blister formation in vivo. In a separate study, Sitaru et al. show for the first time to my knowledge that passive transfer of experimental antibodies against type VII collagen create subepidermal blisters in mice that mimic those seen in patients with epidermolysis bullosa acquisita (see the related article beginning on page 870). While the articles by Liu, Sitaru, and their colleagues identify pathways of inflammation and tissue injury that, if interrupted, may abrogate blister formation, in a third study, Payne et al. utilized phage display technologies to isolate human anti-desmoglein monoclonal antibodies from a patient with pemphigus vulgaris and show that such antibodies have restricted patterns of heavy and light chain gene usage — findings suggesting that autoantibodies may represent an additional target for therapeutic interventions in patients with immunobullous diseases (see the related article beginning on page 888).